2018
DOI: 10.1016/j.labeco.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Single-Sex Schools Successful?

Abstract: We exploit two unusual policy features of academic high schools in Seoul, South Korea-random assignment of pupils to high schools within districts and conversion of some existing single-sex schools to the coeducational (coed) type over time-to identify three distinct causal parameters: the between-school effect of attending a coed (versus a single-sex) school; the within-school effect of school-type conversion, conditional on (unobserved) school characteristics; and the effect of class-level exposure to mixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…In addition, the study revealed that singlesex schooling strengthens females' self-confidence (Eisenkopf, Hessami, Fischbacher, & Ursprung, 2015). Likewise, findings from South Korea documented robust evidence that students in single-sex schools outperform their peers in co-educational schools (Dustmann, Ku, & Kwak, 2018). A study based on a single-sex education program in Chicago called "separating the males from the females" (Patterson, 2012, p. 37) showed that gender separation improves the academic achievement of both females and males.…”
Section: Review Of the Literaturementioning
confidence: 91%
See 1 more Smart Citation
“…In addition, the study revealed that singlesex schooling strengthens females' self-confidence (Eisenkopf, Hessami, Fischbacher, & Ursprung, 2015). Likewise, findings from South Korea documented robust evidence that students in single-sex schools outperform their peers in co-educational schools (Dustmann, Ku, & Kwak, 2018). A study based on a single-sex education program in Chicago called "separating the males from the females" (Patterson, 2012, p. 37) showed that gender separation improves the academic achievement of both females and males.…”
Section: Review Of the Literaturementioning
confidence: 91%
“…Single-sex education exists in both developed, developing, and transitional countries around the world, including Saudi Arabia (Baki, 2004), Malaysia (Jelas et al, 2014), Italy (Contini, Di Tommaso, & Mendolia, 2017), Ireland (Doris, O'Neill, & Sweetman, 2013), the United States (Crawford-Ferre & Wiest, 2013;Pahlke & Hyde, 2016;Patterson, 2012), Switzerland (Eisenkopf, Hessami, Fischbacher, & Ursprung, 2015), and South Korea (Dustmann, Ku, & Kwak, 2018), to cite only a few.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of single-sex education has become an active area of economic research in recent years. See Jackson (2012Jackson ( , 2016, Park et al (2013), Lee et al (2014), and Dustmann et al (2017) for effects of single-sex schooling and Hoxby (2000a), Whitmore (2005), and Lavy and Schlosser (2011) for gender peer effects.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from proposing a robust weighted average method, we also point out the possible inconsistency of the commonly used district(-year) fixed effects estimation under endogenous district selection. This point is neglected in empirical studies on school quality effects that rely on within-district random school assignment (Park et al, 2012(Park et al, , 2013(Park et al, , 2018Lee et al, 2014;Choi et al, 2015;Sohn, 2016;Dustmann et al, 2017;Hahn et al, 2018). This point is also relevant in studies that use the same design as Project STAR and school fixed effects (e.g., Krueger, 1999) and studies that use lottery fixed effects in comparing students who win the lottery for their chosen school with students who lose (Cullen et al, 2006;Deming, 2011;Deming et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation